For the condition that

(3x+y) > (11x - y),

we have

2y > 8x

y > 4x

Under this condition,

y = 3x + y

0 = 3x

0 = x and y > 0

For the opposite condition

(3x + y) < (11x - y)

y < 4x

And

y = 11x - y

2y = 11x

y = (11/2)x

Using this value for y in the relation with x, we have

(11/2)x < 4x

(3/2)x < 0

x < 0

There are no solutions to the equation when x > 0.

(3x+y) > (11x - y),

we have

2y > 8x

y > 4x

Under this condition,

y = 3x + y

0 = 3x

0 = x and y > 0

For the opposite condition

(3x + y) < (11x - y)

y < 4x

And

y = 11x - y

2y = 11x

y = (11/2)x

Using this value for y in the relation with x, we have

(11/2)x < 4x

(3/2)x < 0

x < 0

**When x = 0, the value of y is any non-negative number****When x < 0, the value of y is (11/2)x.**There are no solutions to the equation when x > 0.